ANALYSIS OF INFORMATION TECHNOLOGY GOVERNANCE WITH COBIT 2019 ON THE BAI08 DOMAIN TO IMPROVE HIGHER EDUCATION PERFORMANCE (CASE STUDY: INSTITUT KEGURUAN DAN TEKNOLOGI LARANTUKA) - Hewen, Maria Beliti; Muhammad, Alva Hendi; Nasiri, Asro (STKIP PGRI Tulungagung, 2025)
Information technology governance is essential and must be appropriately managed to fulfill company strategy. Determination of the achievement of the capability level in the information technology governance process at the academic administration bureau at the Institut Keguruan dan Teknologi Larantuka (IKTL) as a case study site. This research aims to analyze the implementation of information technology governance and measure the achievement of capability values using COBIT 2019. The findings of the problem were that an evaluation had never been carried out, and lack of knowledge sharing caused a decrease in the quality of governance, so an evaluation was needed. The research stages help administrative staff responsible for developing and implementing knowledge and presenting information. Information technology management is carried out to facilitate the management, monitoring, and evaluation of each business process and information technology to achieve organizational goals. COBIT 2019 is used to assist organizations in managing and optimizing existing information technology by using factor design to determine important process domains according to the existing circumstances at the institution. Then, the level of capability in the selected domain BAI08 will be analyzed. The results of measuring the level of capability reached a value of 2.25 at level 2 of the expected goals. The solution to overcome the gap is to give recommendations for improving the governance of information technology